Riesgos psicosociales en el desempeño laboral de los servidores públicos y auxiliares de servicio de la Fiscalía de la provincia de Bolívar, en el cuarto trimestre del año 2014. - Encalada Chávez, Liseth Patricia (2016)
The theme is relevant based in the Prosecutorial of the province of Bolivar have influenced psychosocial risks; the problem was to determine how psychosocial risks affect job performance of public service and auxiliary servers; the general objective manifests identifying psychosocial risks in job performance of public service and auxiliary servers; for this the inductive-deductive research methods were used, considering the relations of causality, it is part of general facts to reach particular situations, Analytical-Synthetic, considering that part of the breakdown of each of its parts to study them individually and then in a holistic and comprehensive way, in this case psychosocial risks at work performance to reach the objectives; design research is a field information was obtained on the scene; site survey and the facts happened to public service and auxiliary servers, for their views on the subject investigated and reach the objectives was carried out was evident that psychosocial risk if they influence job performance of workers. The research is descriptive and explanatory; the population was 50 public and auxiliary servers of the prosecutorial of the province of Bolivar. Finally, conclusions are elaborated and recommendations are proposed, the main conclusion is that relate to the problem of psychosocial risks is a major wedges of poor work performance of public service and auxiliary servers and that includes the right job performance good emotional and cognitive stability, psychosocial risks are aspects that harm the physical and mental health of workers, resulting in poor management of emotional intelligence, and hence family problems, we propose a recommendation based on emotional stability in performance labor, to allow for natural and positive attitudes to the facts related to good occupations.